Impact of petroleum and non-petroleum indices on financial development in Oman - Faris Nasif Al-Shubiri; Omar Ikbal Tawfik; Syed Ahsan Jamil (Financial Innovation, 2020)
This study analyzes the impact of petroleum and non-petroleum indices on the financial development of the Sultanate of Oman from 1978 to 2017. To this end, it uses the petroleum proxy of oil rents (% of gross domestic product, GDP) and the non-petroleum proxy of industry (including construction) value added (% of GDP); agriculture, forestry, and fishing value added (% of GDP); and services value added (% of GDP) to determine the effect on financial development, measured by the amount of domestic credit extended to the private sector by banks (% of GDP). It applies an autoregressive distributed lag (ARDL) model. The long-term equation illustrates that the agriculture and industry GDPs have a negative and significant relationship with domestic credit in Oman. However, the oil and service sector GDPs promote financial development. The short-term equation illustrates that the oil, agricultural, and service sectors have positive and significant effects on domestic credit. The conclusion is that the economy of Oman is still in the first phase of economic diversification. Accordingly, the government should use oil revenues to develop various non-oil industrial sectors. This would enhance the country's competitiveness in the global economy and positively contribute to improving the liquidity of the banking sector for stimulating credit at the macroeconomic level.
Keywords: B26; O13; O44; G21; K32; B22; 650; Petroleum index; Non-petroleum index; Financial development; ARDL model; Oman